2015
DOI: 10.1016/j.jpubeco.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Foreign aid and voting in international organizations: Evidence from the IWC

Abstract: I use a unique dispute between major aid donors in the International Whaling Commission (IWC) to investigate whether donor nations change their aid giving in response to changes in aid recipients' voting behavior inside international organizations (IOs). This relationship is difficult to pin down in most IOs because agenda items constantly change and donor coalitions fluctuate with them. I exploit the fact that the IWC has, on the one hand, seen two fixed aid donor blocs opposing each other for three decades o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Also see Novosad and Werker (2018). 27 See Aldenhoff (2007), Kuziemko and Werker (2006), Dreher et al (2008), Kaja and Werker (2010), Fratzscher and Reynaud (2011), Vreeland and Dreher (2014), Dippel (2015), Kilby (2011Kilby ( , 2013Kilby ( , 2015, Kilby (2016, 2019), Malan (2018), and Lang and Presbitero (2018). For a broader overview of the literature on the political economy of international organizations see Dreher and Lang (2019).…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also see Novosad and Werker (2018). 27 See Aldenhoff (2007), Kuziemko and Werker (2006), Dreher et al (2008), Kaja and Werker (2010), Fratzscher and Reynaud (2011), Vreeland and Dreher (2014), Dippel (2015), Kilby (2011Kilby ( , 2013Kilby ( , 2015, Kilby (2016, 2019), Malan (2018), and Lang and Presbitero (2018). For a broader overview of the literature on the political economy of international organizations see Dreher and Lang (2019).…”
Section: Hypothesesmentioning
confidence: 99%
“…This literature typically focusses on individual countries and finds that firms with connections to the country's government receive larger loans (e.g., Khwaja and Mian 2005). 13 A number of papers have shown that countries that are allied with or important for an international organization's major shareholders receive more of the organization's loans at more favorable terms (Thacker 1999, Kuziemko and Werker 2006, Dreher and Jensen 2007, Dreher et al 2009a, 2009b, Dippel 2015. For the IBRD, the IDA, and the IMF, Kaja and Werker (2010), Morrison (2013), and Malan (2016) have shown that country representation on the Executive Boards of these organizations substantially increases the size of the loans that countries receive from them.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a recipient's international standing, its political positions matter as well. Disagreement between donors and recipients on policies significantly lowers aid flows, especially if issues are highly relevant for donors (Andersen et al, 2006;Dippel, 2015;Vreeland and Dreher, 2014). Donors even adjust access to liquidity strategically in order to influence elections in recipients countries.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature documents that donor governments can benefit from their aid deliveries to other countries. For example, aid can promote geostrategic interests (e.g., Bearce and Tirone 2010;Fleck and Kilby 2010), help buy political support in international organizations (e.g., Kuziemko and Werker 2006;Vreeland and Dreher 2014;Dippel 2015;Kersting and Kilby 2016), boost exports (e.g., Martínez-Zarzoso et al 2009Hühne et al 2014), improve the donor country's image (e.g., Dietrich et al 2018;Eichenauer et al 2018), and contribute to regime changes in recipient countries that could align with donor interests (e.g., Bermeo 2011; Kersting and Kilby 2014). However, governments of low-and middle-income countries face strong opportunity costs when spending resources on outgoing development aid rather than investing them in the development of their own countries.…”
Section: Introductionmentioning
confidence: 99%
“…Highlighting the mutual benefit that accrues to donors and recipients, the German Ministry of Economic Cooperation and Development states among its principles that "[d]evelopment cooperation […] also gives a boost to donor countries' economies." See http://www.bmz.de/en/what_we_do/principles/principles-ofdevelopment-policy/index.html (accessed November 27, 2016).21 UNGA voting data is frequently used to measure political relations between countries (e.g.,Alesina and Dollar 2000;Dreher et al 2008;Dippel 2015). We prefer ideal point distances over simple affinity scores as the former use UNGA resolutions that were identical over time to "bridge observations," thus separating shifts in political alignment from mere changes in the UN agenda (e.g.,Davis et al forthcoming).…”
mentioning
confidence: 99%